M-PRMA protocol for vehicular multimedia communication. (2nd December 2009) - Qazi, Bilal R.; Elmirghani, Jaafar M.H.
Medium access control (MAC) protocols, responsible for sharing the channel among users, are receiving more attention especially in vehicular networks due to the highly dynamic nature of the environment in which they operate. Typically MAC protocols were designed for one traffic class such as voice, video or data as all of them have different characteristics. In this paper, we introduce a modified version of packet reservation multiple access namely M-PRMA MAC protocol for vehicular networks responsible for multimedia communication while maintaining quality of service (QoS) for each traffic class. We evaluate the performance of the MAC protocol in terms of packet dropping probability, average delay and throughput under a 3 × 3 km Manhattan grid representing a typical modern city.